Knowing about the Past vs Learning from the Past: We Need to Do Both to Create Effective Policy - Silka, Linda (Maine Policy Review, 2020)
In Maine’s bicentennial year, Executive Editor Linda Silka reflects on the many available sources of information about the state’s past from which we can learn.